Evaluation of genetic variability in Brahman cattle breed in Malaysia using microsatellite markers - Bashir, Haytham Hago Abdelwahid (University of Tlemcen, 2019)
The Brahman was one of the exotic breeds imported into Malaysia to help boost the local beef cattle industry. Due to its adaptability and the productive performance, it is considered as a suitable breed for the country, as well as a breed for use in crossbreeding. This study aimed to assess the genetic variability in the Brahman breed in Malaysia using microsatellite markers. Twenty microsatellite loci,BM1818, BM1824, BM2113, CSRM60, CSSM66, ETH3, ETH10, ETH152, ETH185, ETH225, HAUT24, HAUT27, HEL1, HEL5, HEL9, HEL13, ILSTS005, ILSTS006, INRA005 and INRA023, were used to screen a random sample of 32 of Brahman cattle at the Brahman nucleus herd at DVS Livestock Center in Kuala Berang, Terengganu. A total of 151 alleles were detected. The number of alleles per locus varied between 6 and 10 with an average of 7.6. The effective number of alleles (Ne) range between 2 and 7 with average of 3.8. The observed heterozygosity values (0.26 - 0.83) were lower than the expected heterozygosity values for almost all loci. The overall mean heterozygosity was 0.54. The values of inbreeding coefficient (FIS) based on the individual locus were generally positive. Thirteen loci deviated from HWE equilibrium (p<0.05). This study showed that there was low genetic variability in the Brahman nucleus herd in Malaysia.